Genomic characterization of plasmids harboring blaNDM-1, blaNDM-5, and blaNDM-7 carbapenemase alleles in clinical Klebsiella pneumoniae in Pakistan - Muhammad Usman Qamar; Roberto Sierra; Kokab Jabeen; Muhammad Rizwan; Ayesha Rashid; Yumna Fatima Dar; Diego O. Andrey (Microbiology Spectrum)
ABSTRACT Klebsiella pneumoniae is notorious for causing healthcare-associated infections, which become more complicated by the acquisition of blaNDM genes via mobile genetic elements. Although Pakistan is a well-established hot spot of blaNDM-positive K. pneumoniae, detailed molecular descriptions of blaNDM-carrying plasmids are scarce. Seven K. pneumoniae isolates harboring blaNDM were recovered from clinical sample sources during a 6 month period and tested for antimicrobial susceptibility. A long-read approach was used for whole-genome sequencing to obtain circularized plasmids and chromosomes for typing, annotation, and comparative analysis. The isolates were susceptible to colistin and tigecycline only among the tested antibiotics. We identified five sequence types (STs): ST11, ST16, ST716, ST464, and ST2856. Notably, three strains possessed the hypervirulent capsule KL2, while five were classified as O locus type O2a. Evidence of genetic diversity was further highlighted by the presence of four IncC plasmids harboring blaNDM-1, two IncX3 plasmids harboring blaNDM-5, and a single hybrid IncFIB/IncHI1B plasmid harboring blaNDM-7. These plasmids also carried additional antimicrobial resistance (AMR) genes conferring resistance to aminoglycosides, cephalosporins, and fluoroquinolones. We identified the plasmidome of the K. pneumoniae isolates and characterized the New Delhi metallo-beta-lactamase (NDM)-carrying plasmids. Genetic analysis confirmed the presence of blaNDM-1 and blaNDM-5 on broad host range plasmids and blaNDM-7 in a previously unreported hybrid plasmid backbone. We emphasized the critical role of plasmids in spreading blaNDM in the clinical setting in Pakistan. Hence, we stressed the urgent need for enhanced surveillance, not least in low-middle income countries, infection control measures, and adherence to the “Access,” “Watch,” and “Reserve” guidelines in antibiotics use.IMPORTANCEInfections caused by NDM-producing Klebsiella pneumoniae are a significant challenge to treat and represent a crucial health burden in low- and middle-income countries (LMICs). Most of the blaNDM are located on plasmids that promote horizontal gene transfer. However, there is a lack of comprehensive information on the genetic context of the NDM-carrying plasmids in Pakistan. This study presents a detailed analysis of seven NDM-plasmids in clinical K. pneumoniae isolates, shedding light on their high-risk sequence types and multiple resistance determinants. We also describe the plasmid-bearing NDM alleles (blaNDM-1, blaNDM-5, and blaNDM-7). Notably, we are the first to report blaNDM-7 on the hybrid IncFIB/IncHI1B backbone in Pakistan, a plasmid that has rarely been reported previously globally. Understanding the plasmid genomic landscape is paramount to comprehensively understanding the AMR scenario in this LMIC.